Investigation on energy absorption of natural and hybrid fiber under axial static crushing - Albahash Z.F.; Ansari M.N.M. (Elsevier Ltd, 2023)
Automobile manufacture; Crushing; Energy absorption; Fibers; Reinforced plastics; Automotive applications; Crash energy absorption; Crash worthiness parameters; Different heights; Experimental procedure; Glass fiber reinforced epoxy composites; Hand lay-up; Specific energy absorption; Jute fibers